THE EFFECTIVENESS OF DIAPHRAGMATIC BREATHING & BUTEYKO BREATHING TECHNIQUE IN PATIENTS WITH ASTHMA (The Research of Medical Science Review, 2025)
Background: Asthma is chronic common respiratory condition affecting approximately 300 million people worldwide. Dysfunctional breathing pattern is a common clinical feature in asthmatic patients. Abnormal breathing pattern leads to further pulmonary complications. The aim of this study was to find out the effectiveness of diaphragmatic breathing & Buteyko breathing technique in patients with asthma. Method: 40 Asthmatic patients’ ages 22-67 years were enrolled for the study through convenience sampling. The study duration was 14 days (2 weeks) & the data taken & recorded at day-1 (baseline data) & at the completion of the durations (post-test data after-14 days). The study participants were randomly assigned into groups; control group (n=20) & the treatment group; (n=20). Each study participants were assessed uniformly according to PEFR, FEVI/FVC & FEVI. The obtained comparative data were collected & analyzed by SPSS.22, with P-value <0.05.Results: The study result shows that Buteyko breathing technique in patients with asthma is more statically effective than the diaphragmatic breathingConclusion; Buteyko breathing technique is highly effective than diaphragmatic breathing in patients with asthma.